Additive manufacturing as a sustainability technology in bone tissue engineering: A scientometric analysis in VOSviewer - Siti Rohaida, Mohamed; Saiful Anwar, Che Ghani; Rosli, Yusop (AIP Publishing, 2024)
Bone tissue engineering, combined with advancements in additive manufacturing technologies holds tremendous promise for regenerative medicine applications. However, the sustainable aspect of additive manufacturing in tissue engineering requires further exploration. As the need for producing patient-specific bone implants and scaffolds, there is a growing concern about the environmental impact and cost-effectiveness. This study aims to conduct a scientometric analysis using VOSviewer to explore the research landscape of AM as a sustainable technology in BTE. Research articles were obtained from the Science Direct database. 339 documents were obtained from the initial search. These were systematically filtered for review through the PRISMA framework. The 193 screened articles were quantitatively analysed through the VOS viewer software. This study resulted in the co-occurrence of keywords with additive manufacturing possesses the most occurrence (141 occurrences) and highest total link strength (245), co-authorship of author where A. Zadpoor is the top author, and term co-occurrence with three major clusters. This study’s findings help to develop additive manufacturing in bone tissue engineering and lay the groundwork for future research and innovation in sustainable bone tissue engineering. In conclusion, the application of additive manufacturing technology as a sustainable technology in tissue engineering holds significant promise.